Solubility Studies of Sulfates of Copper, Zinc and Cobalt in Phosphoric Acid at 30 ºC - Samadiy, Murodjon; RAMAZONOVA, DILBAR; UMAROV, SHAVKAT; SHAMISHOVA, AISHOLPAN; MAMATOVA, KHILOLA; AYAKULOV, NURBEK; SAMADIY, MURODJON (Asian Journal of Chemistry, 2023)
Present study reports the isothermal experiments conducted at 30 ºC to ascertain the solubility of copper, zinc and cobalt sulfates in phosphoric acid. The solubility diagram of CuSO4-H3PO4-H2O system is shown to have one branch, this is equivalent to the discharge of copper sulfate pentahydrate into the equilibrium solid phase. The solubility diagrams of zinc and cobalt sulfates have two branches of salt crystallization, corresponding to the release of hexahydrates and monohydrates of zinc and cobalt with increasing phosphoric acid content, saturated solutions in the ZnSO4-H3PO4-H2O and CoSO4-H3PO4-H2O systems become more viscous and denser, reaching a maximum at the transition point, while these indicators in the CuSO4-H3PO4-H2O system only increase.